Heart rate responses during small-sided games and short intermittent running training in elite soccer players: a comparative study - Dellal, A.; Chamari, K.; Pintus, A.; Girard, O.; Cotte, T.; Keller, D. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to compare heart rate (HR) responses within and between physical controlled (short-duration intermittent running) and physical integrated (sided games) training methods in elite soccer players. Ten adult male elite soccer players (age, 26 +/- 2.9 years; body mass, 78.3 +/- 4.4 kg; maximum HR [HRmax], 195.4 +/- 4.9 b[middle dot]min-1 and velocity at maximal aerobic speed (MAS), 17.1 +/- 0.8 km/h) performed different short-duration intermittent runs, e.g., 30-30 (30 seconds of exercise interspersed with 30 seconds of recovery) with active recovery, and 30-30, 15-15, 10-10, and 5-20 seconds with passive recovery, and different sided games (1 versus 1, 2 versus 2, 4 versus 4, 8 versus 8 with and without a goalkeeper, and 10 versus 10). In both training methods, HR was measured and expressed as a mean percentage of HR reserve (%HRres). The %HRres in the 30-30-second intermittent run at 100% MAS with active recovery (at 9 km[middle dot]h-1 with corresponding distance) was significantly higher than that with passive recovery (85.7% versus 77.2% HRres, respectively, p < 0.001) but also higher than the 1 versus 1 (p < 0.01), 4 versus 4 (p <= 0.05), 8 versus 8 (p < 0.001), and 10 versus 10 (p < 0.01) small-sided games. The %HRres was 2-fold less homogeneous during the different small-sided games than during the short-duration intermittent running (intersubjects coefficient of variation [CV] = 11.8% versus 5.9%, respectively). During the 8 versus 8 sided game, the presence of goalkeepers induced an ~11% increase in %HRres and reduced homogeneity when compared to games without goalkeepers (intersubject CV = 15.6% versus 8.8%). In conclusion, these findings showed that some small-sided games allow the HR to increase to the same level as that in short-duration intermittent running. The sided game method can be used to bring more variety during training, mixing physical, technical, and tactical training approaching the intensity of short-duration intermittent running but with higher intersubject variability.